Population census and the question of national cohesion in Nigeria: 1963-2015 (2016)
For over five decades of Nigeria’s independence from the British, the country still faces crisis of disunity among various ethnic groups that make up the country. The manifestations of lack of national cohesion in Nigeria, since the attainment of independence include: political instability, religious and ethnic violence, military intervention in the country’s politics, marginalization, insecurity and struggles for resource control. Historians, political scientists, economists, sociologists and scholars of various disciplines, have through their works, addressed national cohesion question in Nigeria. Federalism, fiscal and political restructuring, conflict resolution, religious tolerance and downplaying of ethnicity, are typical examples of national cohesion question. Similarly, scholars have made attempts at charting new strategies through which the crisis of national cohesion in Nigeria can be ameliorated in its post-independence history. These included the downplaying of the minority agitations, true fiscal federalism, as well as sustainable Federal Character. These intellectual efforts have not beamed their searchlight on the impact of population census on national cohesion question in Nigeria. Thus, the interrogation of a history of population census as a divisive tool that perpetuates unstable political atmosphere in the Nigerian project since independence, seems to have been underestimated. It is against this backdrop that this paper interrogates population censuses, as tools of political instability and political dominance which sustain the question of national cohesion in Nigeria since independence. The paper in its conclusion argues that the politics of population censuses, was part of those divisive structures that have elongated the crises of national cohesion in the country, since the end of colonial rule.